The association of host genes with specific sexually transmitted infections - Bovungana, Qhama; Arumugam, Thilona; Ramsuran, Veron (Frontiers in Reproductive Health, 2023)
Sexually transmitted infections (STIs) are hazardous to human health worldwide. STIs have a direct influence on sexual and reproductive health and can increase the chances of HIV. Globally, more than 1 million STIs are acquired every day and the majority are asymptomatic. Approximately, 374 million cases of STIs have been reported annually. The most prevalent STIs include chlamydia, gonorrhoea, syphilis, and trichomoniasis. These STIs are caused by Chlamydia trachomatis, Neisseria gonorrhoeae, Treponema pallidum and Trichomonas vaginalis. The major factor that contributes to the susceptibility and prognosis of infectious diseases is genetic variation. Host genes play a huge role in STIs and immune response. The production of host factors is stimulated by a variety of bacteria, viruses and parasites and the host factors can play a role in increasing host vulnerability to infection and pathogen persistence. Genetic variation or polymorphisms within certain host genes can influence the course of pathogen infection and disease progression. Polymorphisms can contribute to changes in gene expression and or changes in the protein structure. which may either contribute to/or protect against infection. This review discusses the role of host genes in influencing the susceptibility of the most prevalent STIs caused by Chlamydia trachomatis, Trichomonas vaginalis, Treponema pallidum and Neisseria gonorrhoeae. We evaluate polymorphisms associated pathogen recognition signalling pathway of these diseases. These polymorphisms may be used as biomarkers to infer risk to specific STIs.